(untitled) - Smith, William F. (Boston, 2006)
For this fourth edition of a text/CD-ROM package for an introductory course in materials science and engineering, Smith (University of Central Florida) and Hashemi (Texas Tech University) have added three new sections devoted to advanced alloys and their applications in biomedical engineering. There are now 1,200 problems and 180 materials selection and design exercises. The CD-ROM, new to this edition, contains video labs and a companion lab manual, visualization software allowing students to create and view crystal structures and molecules, animations and tutorials, and a database of material properties.
Keywords: Materials science,Materials; Khoa học vật liệu